Alat Penghitung Barang Secara Otomatis Menggunakan Sensor Infrared Berbasis Arduino Uno - Al Husain; David Calvin Siregar; Septian Heri Permadi (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
In electronics technology, the performance of a sensor in gathering information to detect objects is very important. Infrared sensor has the same properties as a transistor, which produces a cut-off, which means the light sensor will turn on if an item is detected and the data will come out in the form of LOW logic otherwise the lamp will remain off if the item is not detected and the data that comes out has a logic value HIGH. The distance range of the sensor or the level of sensitivity of the sensor can be adjusted via Potensio. The item count report is managed by Arduino which is processed in information in the form of data on the number of goods entering and exiting goods. The method applied in this study uses the System Development Life Cycle (SDLC) Method with a Waterfall modification that is expected to be able to easily determine the achievement of a system. Based on testing in terms of component functionality connected to the prototype system has worked well, while testing in terms of usability that the system is easily used efficiently